1990
DOI: 10.1038/345634a0
|View full text |Cite|
|
Sign up to set email alerts
|

The LDL receptor pathway delivers arachidonic acid for eicosanoid formation in cells stimulated by platelet-derived growth factor

Abstract: Animal cells can convert 20-carbon polyunsaturated fatty acids into prostaglandins (PGs) and leukotrienes. These locally produced mediators of inflammatory and immunological reactions act in an autocrine or paracrine fashion. Arachidonic acid (AA), the precursor of most PGs and leukotrienes, is present in the form of lipid esters within plasma lipoproteins and cannot be synthesised de novo by animal cells. Therefore, AA or its plant-derived precursor, linoleic acid, must be provided to cells if PGs or leukotri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 19 publications
1
36
0
1
Order By: Relevance
“…Interestingly, the amount of 15( S )-HETE in the 15-LO-1 RAW increased with cholesterol loading via acLDL. These data are consistent with that of Habenicht et al ( 26 ) who showed that LDL delivers arachidonic acid for prostaglandin biosynthesis in fi broblasts.…”
Section: Resultssupporting
confidence: 83%
“…Interestingly, the amount of 15( S )-HETE in the 15-LO-1 RAW increased with cholesterol loading via acLDL. These data are consistent with that of Habenicht et al ( 26 ) who showed that LDL delivers arachidonic acid for prostaglandin biosynthesis in fi broblasts.…”
Section: Resultssupporting
confidence: 83%
“…PAF-AH resides on dLDL, 22,29 and LDL particles are an important source for the essential compound arachidonic acid. 31 Therefore, we have suggested that dLDL may contribute to atherogenesis by functioning as a vector that provides both the essential substrate and the crucial enzyme activity necessary for prostaglandin synthesis. 22 This concept would acknowledge PAF-AH as having an active role in atherogenesis rather than being a mere risk marker.…”
Section: Discussionmentioning
confidence: 99%
“…AA is then present in serum either as an albumin-bound acid, or as part of lipids present in lipoproteins. Habenicht et al (1990) have demonstrated that cholesteryl-AA is taken up by the cells via the LDL receptor pathway. Serum albumin-bound AA enters the cells by endocytosis (Geuskens et al, 1994;Iturralde et al, 1991;Uriel et al, 1994).…”
Section: Discussionmentioning
confidence: 99%